The role of critical reflection as an employability skill in sport management. Issue 2 (15th March 2021) - de Schepper, Jos; Sotiriadou, Popi; Hill, Brad
ABSTRACT: Research question: The two research questions driving this study were (1) 'To what extent do sport management students address the individual and social dimensions of critical reflection during work-integrated learning (WIL) experiences?', and (2) 'Do these skills align with what employers need from those working and seeking employment in the sport industry?'. Research methods: A total of 314 WIL stakeholders (i.e. students, Academic Supervisors and Industry Supervisors) representing 20 tertiary sport management institutions in the Netherlands participated in the study's questionnaire. The purpose was to identify the potential differences across perceptions of three stakeholder groups on the extent to which students address the individual and social dimensions of critical reflection and the ways critical reflection skills align with the sport management industry needs. MANOVA and separate ANOVA tests compared perceptions on students' integration of three individual and three social dimensions of critical reflection. Results and findings: Results showed disparities between perceptions on the extent to which students critically reflect. Industry Supervisors perceived students only addressed two of six dimensions of critical reflection (i.e. asking for feedback and reflecting on career ambitions). Findings in this study are consistent with other empirical evidence concerned with graduates' level of key employability skills and highlight the need to strengthen the development and alignment of social critical reflection skills with sport industry employer needs. Implications: This study addresses the need to align sport management graduates skill set with sport industry workforce needs and enhance graduate employability. The classification of critical reflection skills into six dimensions offers a useful guide to sport organisations and helps assess which dimensions require attention or further development.